Indigenous Fuel-wood Species from Western Ghats of Maharashtra - Ghate, V. S.; Vartak, V. D.; Kumbhojkar, M. S. (Indian Forester, 1990)
Several non-conventional plant species are preferred by villagers in Western Maharashtra for fuel-wood besides commercial ones. An attempt has been made to record these local species with their fuel characteristics. The paper describes 38 indigenous fuel-wood species commonly used by village communities from areas of Western Ghats of Maharashtra. These data have relevance for selecting indigenous species for planning energy plantations and thereby, minimizing the fuel-wood crisis.